Physiological and performance responses to the FIFA 11+ (part 2): a randomised controlled trial on the training effects - Impellizzeri, F. M.; Bizzini, M.; Dvorak, J.; Pellegrini, B.; Schena, F.; Junge, A. (Journal of Sports Sciences, 2013)
The aim of this study was to examine the training effects of an injury prevention programme on neuromuscular control, strength and performance in male amateur football players.